The Role of Policy Instruments on the Pattern of Diffusion: The Case of Solar Photovoltaic in Asia Pacific (European Journal of Marketing and Economics, 2024)
While an increasing number of literature investigates the role of policy instruments on the renewable energy technologies (RETs) investment, the effect of policy instruments on the pattern of diffusion on RETs remain understudied. Therefore, this paper explores the effectiveness of the policy instruments on the pattern of diffusion of solar PV capacity for a set of 6 Asia Pacific countries from 2000 to 2015. The present study is different from previous literature by exploring the effect of policy inducement namely subsidies and tax incentives on the pattern of diffusion of solar PV. The analysis is performed by estimating a diffusion of innovation equation using a pooled OLS model. Results indicate the behaviour of previous adopter and policy intervention does reflect individuals’ tendency to switch to the PV technology. In detail, the existence of tax incentives promotes the shift of solar PV capacity during the analysis period. By exploring the effect of policy inducement on the pattern of diffusion, there is a potential for the current policy to be introduced at the states level to facilitate the diffusion of solar PV.
Keywords: Bass diffusion, renewable energy policy, renewable energy technology diffusion, tax incentive, subsidy, solar energy